Identificação das inovações : um estudo de caso nos hospitais que integram o sistema de saúde de Caxias do Sul - RS - Weiand, Simone Grun (My University, 2014)
The Brazilian Federal Constitution, promulgated in 1988, on its 196 article ensures that health is everybody´s right and a state duty. The government management structure and its public policies have been influenced by health themes, so being addressed to innovation and competitiveness in Brazil. Innovation is an implementation of a new product (benefit or service) either significantly improved, or a new process, or a marketing method, or a new organizational method of business practice. From the relevance of the issues related to health in the Brazilian historical and economical context, particularly in Caxias do Sul, and from the importance of innovation for the organizations it has been carried out a scientific study so as to search for a better understanding on the subject, identifying the innovations that have taken place in six out of seven hospitals members of the Caxias do Sul Health System. The methodology used has been based on qualitative research of multiple case studies, exploratory type, through in-depth interviews with managers from the participant hospitals. The contents proceeding from the interviews have been undergone to a content analysis, showing that every hospital that has participated on the study has innovated during the research period. There have been thirty-five identified innovations, namely, ten product; ten process; four marketing, and eleven organizational innovations. Management is the chief factor for innovation. Demand has been the main reason that has led hospitals to innovate their product; the process innovations have been brought about due to humanization, agility, and management. To innovate in marketing, hospitals have made use of sustainability, demand, and brand strengthening. Concerning to the sector where the innovations have taken place, it has been observed that, fifteen out of thirty-five identified innovations, have been implemented in every sector, and besides the others occurred in several hospital sectors. Twenty-three innovations have been classified as radical, and twelve as incremental and twenty-four are brand-new for the organization, remaining eleven as brand-new for the market. Finally, it has been pointed out some limitations on the investigation, as well as future research possibilities.
A Constituição Federal do Brasil, promulgada em 1988, no seu artigo 196 garante que saúde é um direito de todos e dever do Estado. A estrutura administrativa do governo e as políticas públicas têm sido influenciadas por temas de saúde, sendo direcionadoras da inovação e da competitividade no Brasil. A inovação é a implantação de um novo produto (bem ou serviço) ou significativamente melhorado, ou de um novo processo, ou de um novo método de marketing, ou um novo método organizacional na prática de negócios. Partindo da relevância das questões relacionadas à saúde no contexto histórico e econômico do Brasil, em especial na cidade de Caxias do Sul, e da importância da inovação para as organizações foi feito um estudo científico com a finalidade de buscar um melhor entendimento sobre o tema, identificando as inovações ocorridas em seis dos sete hospitais integrantes o Sistema de Saúde de Caxias do Sul (SSCX). A metodologia utilizada tem como base a pesquisa qualitativa de estudo de múltiplos casos, de caráter exploratório, por meio de entrevistas individuais em profundidade com os gestores dos hospitais participantes. Os conteúdos provenientes das citadas entrevistas foram submetidos à análise de conteúdo, demonstrando que todos os hospitais participantes do estudo inovaram no período pesquisado. Foram trinta e cinco as inovações identificadas, sendo dez inovações de produto, dez de processo, quatro de marketing e onze organizacionais. A gestão é o fator preponderante para a inovação. A demanda foi o principal motivo que levou os hospitais a inovarem em produto; as inovações de processo foram motivadas pela humanização, agilidade e gestão. Para inovar em marketing, os hospitais valeram-se da sustentabilidade, demanda e fortalecimento da marca. Quanto ao setor em que ocorreram as inovações, observou-se que quinze, das trinta e cinco inovações identificadas, foram implementadas em todos os setores, sendo que as demais ocorreram em vários setores do hospital. Vinte e três inovações foram classificadas como radicais e doze como incrementais e vinte e quatro são novas para organização, restando onze como novas para o mercado. Por fim, apontam-se algumas limitações na investigação, bem como possibilidade de pesquisas futuras.
Keywords: Administração; Saúde; Saúde; Sistema de saúde; Inovação; Sistema de inovação; Saúde pública; Hospitais; Caxias do Sul (RS); Health; Health system; Innovation; Innovation system; Public health; Hospitals